Visualization of Myocardial Damage Based on Surface Heart Model - F. A., Satybaldiyeva; K. A., Ozhikenov; R. N., Beysembekova; Oleg, Bodin; G. Zh., Yessenbekova; A. K., Kultas (Journal of Applied Robotics and Artificial Intelligence, 2023)
The visual presentation of the results of the analysis of cardio graphic information is an important element of the diagnostic process. The article discusses the issues of visualization of the state of the heart, notes the importance of a visual representation of the processes of the functioning of the heart for diagnosis. The Delaunay triangulation is considered and it is proved that on its basis it is possible to approximate an arbitrarily complex surface. An algorithm for constructing a surface model of the heart based on Delaunay triangulation has been developed. The issues of texture generation are covered in detail. The texture is a convenient tool for displaying the state ofthe heart, as it allows you to visually show the place of possible damage on the surface of the heart.
Keywords: Delaunay triangulation; surface model of the heart; texture mapping.